UNCOVERING TRANSPARENCY IN BIODIVERSITY ACCOUNTING STANDARDS IN INDONESIA’S MINING SECTOR - Simon Nisja Putra Zai; Yuni Pristiwati Noer Widianingsih (Accounting Profession Journal (APAJI))
This study examines the transparency of biodiversity reporting by mining companies in Indonesia based on the Global Reporting Initiative (GRI) guidelines. Using a qualitative approach, this study analyzed 60 sustainability reports from 30 mining companies listed on the Indonesia Stock Exchange (IDX) in the 2022-2023 periods. The results showed that the level of biodiversity reporting was still low, where out of 30 GRI indicators; only 11 indicators (36.67%) were reported. These results show that the company is more focused on short-term operational and reputational issues than long-term strategic efforts.